The Influences of Communication and Decision Making at Senior High School to Teacher’s Performance in East Aceh Regional - Abidah Abidah; Yusrizal Yusrizal; Nasir Usman (Proceedings of AICS - Social Sciences, 2020)
This study aims to obtain an overview of the influence of communication and decision making on senior high school teacher’s performance at East Aceh Regional. This research was survey research involving ten principals, 20 vice principals, 30 teachers, and 30 students. This study consisted of independent variables, i.e., communication (X1) and decision making (X2), and the dependent variable, i.e., teacher performance (Y). The results showed that communication and decision making significantly influenced teachers’ performance. Therefore, the Schools in East Aceh Regional should maintain and improve the current effective communication and decision making to increase teachers’ performance.